The prognostic value of toll-like receptor5 and programmed cell death-ligand1 in patients with peripheral T-cell non-Hodgkin lymphoma. Issue 11 (19th September 2019) - Sun, Mengqi; Su, Wenjia; Qian, Jingrong; Meng, Hongxue; Ji, Hongfei; Liu, Yupeng; Zhang, Yue; Li, Wenhui; Zhang, Qingyuan; Zhao, Shu
Abstract: TLR5 is expressed in a variety of tumors. However, the clinical impact of TLR5 in Peripheral T-cell non-Hodgkin lymphomas (PTCLs) remains unclear. We analyzed differentially expressed genes in PTCLs samples from Gene Expression Omnibus database. We examined TLR5 and programed cell death-ligand1 (PD-L1) expression by immunohistochemistry in PTCLs tissues. Gene expression profiling shown PD-L1 and TLR5 expression was higher in PTCLs than in normal samples. The rates of high TLR5 and PD-L1 expression were 12.5% and 45.8%. We found association between TLR5 and PD-L1 expression. Low TLR5 expression or high PD-L1 expression was correlated with shorter overall survival and inferior disease-free survival. Multivariate Cox regression analysis shown low TLR5 expression, high PD-L1 expression, gender, and high IPI score were prognostic factors ( p  < .05). PTCLs patients with low TLR5 expression and high PD-L1 expression had worse prognosis. TLR5 and PD-L1 may serve as potential therapeutic targets in PTCLs patients.